Indirect to direct band gap transition and excellent optical properties in novel MoSi2N4-BP bilayer and trilayer vdW heterostructures - Bromand Nourozi; Farhad Khoeini; Arash Boochani (Scientific Reports)
Abstract Multilayer van der Waals (vdW) heterostructures, composed of different atomically thin films, exhibit a wide range of fascinating phenomena with diverse applications. Here, we propose the existence of bilayer (MoSi2N4/BP) and trilayer (BP/MoSi2N4/BP and MoSi2N4/BP/ MoSi2N4) vdW heterostructures of MoSi2N4 and BP. We investigate structural, electronic, and optical properties of the structures using first-principles calculations based on density functional theory (DFT). Our results shows that the BP/MoSi2N4/BP heterostructure is the most stable. All investigated heterostructures exhibit semiconducting behavior with a direct band gap at the K-point. Optical analysis reveals that they have the lowest energy loss function (ELF) in the IR and visible light regions, along with high reflectance in non-transparent regions. In addition, the heterostructures exhibit high optical absorption compared to their components, even in the visible light spectrum. These heterostructures have great potential for applications in nanoelectronics, optoelectronics, and photocatalysis, including solar energy conversion, sensing, and hydrogen evolution.